Pengembangan Aplikasi Mobile Pendeteksi Penyakit pada Tanaman Cabai dengan menggunakan Teknologi Clarifai - Insan Nurzaman Bangga Adi Pratama; Issa Arwani; Handoko Handoko (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
In tropical countries like Indonesia, plants are commercial crops that are widely cultivated and have high selling points so that they are profitable for farmers. Based on data from the Ministry of Agriculture, the amount of chili production every year is still fluctuating, ie experiencing an increase or decrease. One obstacle that is often encountered is the lack of knowledge of farmers in recognizing the types of diseases and pests that attack plants on chilies. Based on these problems, the authors take advantage of the opportunity to develop a mobile application with the Android operating system that is useful for detecting diseases in chili plants and its control. This application utilizes clarifai technology to help detect images on input from user devices through images or galleries. The development of this application uses the Waterfall method. The validation test results are 100%. The accuracy of the test results in this application is 79%. The usability test results in this application are 82.75%. While in compatibility testing, the application can run in accordance with the predetermined Android minimum SDK 23 level.